The Investigation of Field Plate Design in 500 V High Voltage NLDMOS - Donghua Liu; Xiangming Xu; Feng Jin; Wenting Duan; Huihui Wang; Jing Shi; Yuan Yao; Jun Hu; Wensheng Qian; Pengfei Wang; David Wei Zhang (Advances in Condensed Matter Physics)
This paper presents a 500 V high voltage NLDMOS with breakdown voltage (VBD) improved by field plate technology. Effect of metal field plate (MFP) and polysilicon field plate (PFP) on breakdown voltage improvement of high voltage NLDMOS is studied. The coeffect of MFP and PFP on drain side has also been investigated. A 500 V NLDMOS is demonstrated with a 37 μm drift length and optimized MFP and PFP design. Finally the breakdown voltage 590 V and excellent on-resistance performance (Rsp = 7.88 ohm * mm2) are achieved.